Estimating the date of origin of an HIV-1 circulating recombinant form - Tee, K.K.; Pybus, O.G.; Parker, J.; Ng, K.P.; Kamarulzaman, A.; Takebe, Y. (2009)
HIV is capable of frequent genetic exchange through recombination. Despite the pandemic spread of HIV-1 recombinants, their times of origin are not well understood. We investigate the epidemic history of a HIV-1 circulating recombinant form (CRF) by estimating the time of the recombination event that lead to the emergence of CRF3301B, a recently described recombinant descended from CRF01AE and subtype B. The gag, pol and env genes were analyzed using a combined coalescent and relaxed molecular clock model, implemented in a Bayesian Markov chain Monte Carlo framework. Using linked genealogical trees we calculated the time interval between the common ancestor of CRF3301B and the ancestors it shares with closely related parental lineages. The recombination event that generated CRF3301B (t(rec)) occurred sometime between 1991 and 1993, suggesting that recombination is common in the early evolutionary history of HIV-1. The proof-of-concept approach provides a new tool for the investigation of HIV molecular epidemiology and evolution. (C) 2009 Elsevier Inc. All rights reserved.